A comprehensive study of celastrol metabolism in vivo and in vitro using ultra‐high‐performance liquid chromatography coupled with hybrid triple quadrupole time‐of‐flight mass spectrometry. Issue 6 (12th February 2022) - Zhang, Xiao‐wei; Chen, Yu‐ting; Feng, Xue; Li, Lu‐ya; Song, Ke‐wei; Sun, Yu‐peng; Zhang, Guo‐hua; Zhang, Lan‐tong
Abstract: Celastrol has attracted great attention owing to its anti‐arthritis, antioxidant, and anticancer activities. Nevertheless, its metabolism in vivo (rats) and in vitro (rat liver microsomes and intestinal flora) has not been comprehensively characterized. In this study, ultra‐high‐performance liquid chromatography coupled with hybrid triple quadrupole time‐of‐flight mass spectrometry was used as a rapid and sensitive approach for studying the metabolism of celastrol in vivo and in vitro. A total of 43 metabolites were identified and characterized. These include 26 metabolites in vivo, and 28 metabolites in vitro (nine metabolites in rat liver microsomes and 24 metabolites in rat intestinal flora). Additionally, the celastrol‐biotransformation capacity of the intestinal tract was confirmed to exceed that of the liver. Furthermore, the metabolic profile of celastrol is summarised. The information obtained from this study may provide a basis for understanding the pharmacological mechanisms of celastrol and will be beneficial for clinical applications.